Criminal Disparities in the Judiciary in Tasikmalaya City (Study of Decision No. 113/Pid.Sus/2020/PN.Tsm and No. 114/Pid.Sus/2020/PN.Tsm) - Henidar Anindita (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
Different conviction or disparity of sentencing in judges discretionary form at imposing of judgment for making a decision. This case impacts disappointment for the general public and especially for conviction. This research purposes to know the rule of sentencing disparity on criminal law in Indonesia. Furthermore, some factor sentencing disparity happened in the article No. 113/Pid.Sus/2020/PN.Tsm and article No. 114/Pid.Sus/2020/PN.Tsm in narcotic crime case at Tasikmalaya. This research uses a normative juridical method done through literature study that analyzes secondary data in the form of laws and regulation, legal document, the result of research, assessment of result and others reference through interview. This study's results are: 1) The rule of disparity of sentencing criminal procedural law in Indonesia list in article 197 KUHP, judges must consider determining strafmaat for defendant through material evidence at trial to support the conclusion considerate of judges. There is a limit of judges to deciding cases that regulate in article 183 KUHAP. 2) Factor of sentencing disparity in the article No. 113/Pid.Sus/2020/PN.Tsm and article No. 114/Pid.Sus/2020/PN.Tsm in narcotic crime case, there is other evidence from each defendant that makes the basis of consideration is different. However, the defendant's role in committing a crime was some in the article No. 35 Tahun 2009 about Narcotic regarding provisions of the crime. The researcher suggests that when judges decide the matter that contained disparity of sentencing, accordingly, it must rely on objective consideration.Keywords: Disparity of Sentencing, Conviction, Narcotic.